The beginning of Islamic architecture and its impact to Indian and Central Asian architecture - Rahimov, Laziz; Mohd Nawawi, Norwina; Ilhom, Maxmatqulov; Luqmonov, Dilshod; Dilrabo, Kholdorova; Marjona, Kamilova (Genius Journals Publishing Group, 2023)
In given article we will try to analyze of Islamic architecture and it`s evolution process. Moreover, we will try to clear up the role of Islamic architecture in formation Central Asian and Indian architecture. Lastly, we describe how Islamic buildings has been created and its development over the years, also, we have given evidence supporting our points.